Advances and challenges in plant N-glycoengineering: when fucosylation matters - Gauba, Kavya; Kunnummel, Vinny; Castilho, Alexandra (Frontiers in Plant Science, 2025)
Plant-based expression systems have emerged as promising platforms to produce recombinant glycoproteins. Transient recombinant protein production is a promising alternative to stable transgenic systems, particularly for emergency situations in which rapid production of novel therapeutics is needed. A potential barrier for plant-based production of therapeutic proteins is that different glycosylation patterns are found on plants. Nevertheless, advances in glycoengineering, particularly in the generation of glycoproteins bearing human- and helminth-like N-glycans, further support the use of plants as valuable systems for biopharmaceutical manufacturing. Glyco-design, including methods to control glycan structures and distributions in plants, is a powerful tool for optimizing the efficacy of therapeutic glycoproteins. However, glycoengineering is not merely a matter of gene knock-in or knock-out and it often requires precise fine-tuning to prevent the formation of aberrant glycan structures. Strategies to address these challenges include: (i) identifying and modulating the activity of proteins/enzymes involved in aberrant glycosylation, (ii) optimizing the subcellular localization and expression levels of glyco-modifying enzymes, (iii) inhibiting glycosidases that trim terminal sugar residues, and (iv) enhancing the accessibility of glycosylation sites to processing enzymes. This review summarizes key developments and challenges in plant N-glycoengineering. Within this broad framework, we highlight core α1,3-fucosylation as a representative case illustrating how a single glycan modification can alter structural accessibility, enzyme activity, and overall glycan maturation.